You (you).'- Lee Kit. Pavilion of Hong Kong : 55th International Art Exhibition- La Biennale di Venezia 2013 - Lars Nittve; Lee Kit; Yung MA (West Kowloon Cultural District Authority; Hong Kong Arts Development Authority, 2013)
"You (you)." sheds light on Lee's practice by emphasising his approach to space, colour, texture and materiality. His seemingly minimal installations are strongly connected to the rituals of daily life. From hand-painted cloths and cardboard paintings, to ready-made objects and found imageries, Lee's work has continuously questioned the common perceptions of ordinary materials, transforming their mundanity into a series of visual dialogues that is subtle and resonant.' (excerpt from p. 2) This catalogue accompanies Lee Kit's 'You (you).' at the 55th International Art Exhibition of Venice Biennale, from 1 June to 24 November 2013. Featured are nine works from Lee's exhibition, as well as essays and an artist interview.
English; Chinese
Keywords: N4390-5098 Visual Arts- Exhibitions; Pavilion catalog; Hong Kong